Growth architecture and silhouette of Jurassic conifers from La Matilde Formation, Patagonia, Argentina - Falaschi, Paula (2011)
Simple morphological traits are used to describe the architecture of a tree: the growth and branching process, the morphological differentiation of the axes and the position of reproductive structures. The main purpose of this contribution is to describe the growth architecture of the Jurassic conifer trees present at the most basal part of the La Matilde Formation in the locality of Monumento Natural Bosques Petrificados, Patagonia, Santa Cruz province, Argentina, and to compare it with that of extant and fossil conifers. This study is based on a large number of in situ petrified trunks, impressions and external molds of leafy branches and female cones in intimate association or organic connection with the trunks. The cones were assigned to Araucaria cf. A. mirabilis (Speg.) Windhausen emend. Calder (Araucariaceae) based on morphological and anatomical characters. The "Araucaria mirabilis" trees had 3 branching categories, corresponding to the typical pattern in extant Araucariaceae, although 4 branching categories cannot be completely discarded. The main, orthotropic stem (TA1) had rhythmic growth and branching, bearing 3-4, probably up to 6-7 plagiotropic branches in pseudowhorls. The lower part of the trees shows no branch-scars; therefore, self-pruning would have been present. Lateral branches (A2) had rhythmic branching: the branchlets (A3) were distributed regularly on the leading branch, with an alternate arrangement, conforming two orthostichies on the same horizontal plane. The female cones were borne terminal at the tip of peduncles, but lateral in position with respect to A2 branches. Reiteration patterns are present: total reiterations (bifurcated trunks and big, orthotropic branches in trunks with normal plagiotropic branches) and partial reiterations (epicormic branching) were observed. The root system consisted of 6 horizontal roots, no tap root was observed. Two architectural patterns or "morphotypes" were recognized at one of the forest levels studied, in keeping with other pieces of evidence (type of wood, foliage, and cones). The "Araucarioid morphotype or morphotype A" includes most of the studied specimens (i.e. "Araucaria mirabilis" trees); showing pseudowhorls of plagiotropic branches. These characters correspond to Massart's model, with certain modifications in the adult trees due to reiteration processes. Morphotype B was observed in bigger trunks with a distinctive costulated surface, which bear only orthotropic branches irregularly arranged, and without reiteration evidences; they could be assigned to Attim's model and possibly represent a different conifer taxon, though subrepresented. Partial and total reiteration patterns are described for the first time for Jurassic, Gondwanic conifers. Moreover, Massart's model can be followed from Upper Palaeozoic Walchiaceae to Mesozoic Araucariaceae.